Pengaruh Product Quality Brand Image Dan Promotion Terhadap Purchase Decision Studi Kasus Pada Umkm Kafe Cangkir Dampit Kec. Dampit, Kab. Malang - Darmawan, Alvian; Wahono, Budi; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to find out how much Product Quality, Brand Image, and Promotion Influence on Purchase Decision Case Study on Cangkir Dampit Cafe Dampit District, Malang Regency. The number of samples was determined using the Malhotra formula and the results were obtained as many as 85 respondents. The data was obtained by distributing questionnaires to buyers at the Cangkir Dampit Cafe which was selected by accidental sampling. The data analysis in this study uses SPSS version 25. The data testing techniques used in this study include validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis test, f test, t test and determination coefficient test (R2). The results of this study show that Product Quality, Brand Image, and Promotion have a significant effect on Purchase Decision. Keywords: Purchase Decision, Product Quality, Brand Image ,Promotion